Response of different drip irrigation volumes and mulches on yield of fennel (Foeniculum vulgare) in western part of Rajasthan (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted at Research Farm College of Agriculture, S.K. Rajasthan Agricultural University, Bikaner to evaluate the different drip irrigation volume and mulches on growth and yield of fennel. The experiment was carried out in split plot design with three replications. There were five treatment viz. drip at 1.0, 0.85, 0.70 and 0.55 and surface irrigation in main plots and mulches viz. organic mulch, polythene mulch and with out mulch were used in sub plots. The height of plant was maximum (130 cm) with 1.0 volume of drip than the other volume of drip and surface irrigation. When water volume of drip was decrease from 1.0 to 0.55 the plant height was similarly reduced and height was also recorded maximum with polythene mulch. The highest yield and water use efficiency was obtained under the 0.55 volume of drip (14.72q/h) however it was recorded minimum (8.62q/h) in surface irrigation. In mulches, yield and water use efficiency was recorded in Polythene mulches.
Keywords: Fennel; drip irrigation; mulch